The occupational health nurse in Natal - B.N. Hunt; L. Grainger (AOSIS, 1983)
The Commission of Enquiry on Occupational Health, appointed in 1975, published its findings in 1976. The general impression gained by members of the Commission, after a series of visits and interviews pertinent to the field, is summed up thus in the fourth chapter of the Report: Although industrialists in the Republic and the Territory of South-West Africa are aware of the workers' position, it has regrettably to be stated categorically that, except in the mining industry, industrial health not only occupies a secondary position in industry in this country, but that industrialists have put very little time, money and organisation into the prevention of occupational diseases (Erasmus 1976).